Gastric Adenocarcinoma with Thymic Metastasis after Curative Resection: A Case Report - Matsunaga, Tomoyuki (The Korean Gastric Cancer Association, 2014)
The peritoneum is the most frequent site of recurrence for gastric cancer after gastrectomy, followed by the liver and lymph nodes. In contrast, metastasis to the thymus is rare. Annual surveillance with computed tomography was performed on a 67-year-old man who previously underwent a distal gastrectomy and D2 lymph node dissection for gastric cancer at Tottori University. Five years after the initial operation, an anterior mediastinal tumor was detected by computed tomography. The patient underwent video-assisted thoracic surgery to remove the tumor. Histopathology revealed adenocarcinoma cells similar to those of the gastric cancer resected 5 years previously. Thymic metastasis was considered likely based on the location of the tumor. The recognition that gastric cancer can metastasize to unusual anatomic locations, such as the thymus, can facilitate an accurate, prompt diagnosis and appropriate treatment.